The impact of basketball coach`s leadership style on perfectionism of basketball players - Capric, I.; Stankovic, M.; Ðordevic, D.; Spirtovic, O.; Mavric, A.; Zecirovic, A.; Demirovic, D.; Cular, D.; Jelaska, I.; Tomljanovic, M.; Sportis, G. (Journal of Physical Education and Sport, 2023)
Leadership in sports is a collaborative, cooperative, and interactive process between coaches and athletes. A coach`s most important abilities include athlete motivation, creating a productive environment in the group, and pursuing success. The aim of this research was to determine the influence of the coach's leadership style on basketball players' perfectionism. The sample of participants for the purposes of this research consisted of 104 respondents (51 male, 53 female), who play the second rank of the national competition. In order to examine the coach's behavior, the online questionnaire Leadership Scale for Sport and Competitive perfectionism Scale was used to determine the positive and negative dimensions of competitive perfectionism. The influence of leadership style on the pursuit of perfectionism and changes in the values of the pursuit of perfectionism is determined by changes in instructiveness 7.1%, democratic behavior 16.9%, autocratic behavior 26.3%, social support 16.5% and positive feedback 33.6 %. The obtained results indicate the influence of leadership style on the perfectionism of the basketball players and statistical significance, and that each coach type tends towards per-fectionism and it is not possible to generalize which style is more appropriate in which situation. The impact on the scale of competitive perfectionism and changes in the values of striving for perfectionism was determined by changes in instructiveness 3.1%, democratic behavior 5.6%, autocratic behavior 8.3%, social support 1.9% and positive feedback 10.3%. Based on the obtained results, we conclude that autocratic behavior (8.3%) and positive feedback (10.3%) showed statistically significant values in relation to other values of the coach's behavior style on competitive perfectionism.